Widespread and extensive lengthening of 3′ UTRs in the mammalian brain - Miura, Pedro; Shenker, Sol; Andreu-Agullo, Celia; Westholm, Jakub O.; Lai, Eric C. (Genome Research, 2013)
Remarkable advances in techniques for gene expression profiling have radically changed our knowledge of the transcriptome. Recently, the mammalian brain was reported to express many long intergenic noncoding (lincRNAs) from loci downstream from protein-coding genes. Our experimental tests failed to validate specific accumulation of lincRNA transcripts, and instead revealed strongly distal 3′ UTRs generated by alternative cleavage and polyadenylation (APA). With this perspective in mind, we analyzed deep mammalian RNA-seq data using conservative criteria, and identified 2035 mouse and 1847 human genes that utilize substantially distal novel 3′ UTRs. Each of these extends at least 500 bases past the most distal 3′ termini available in Ensembl v65, and collectively they add 6.6 Mb and 5.1 Mb to the mRNA space of mouse and human, respectively. Extensive Northern analyses validated stable accumulation of distal APA isoforms, including transcripts bearing exceptionally long 3′ UTRs (many >10 kb and some >18 kb in length). The Northern data further illustrate that the extensions we annotated were not due to unprocessed transcriptional run-off events. Global tissue comparisons revealed that APA events yielding these extensions were most prevalent in the mouse and human brain. Finally, these extensions collectively contain thousands of conserved miRNA binding sites, and these are strongly enriched for many well-studied neural miRNAs. Altogether, these new 3′ UTR annotations greatly expand the scope of post-transcriptional regulatory networks in mammals, and have particular impact on the central nervous system.
10.1101/gr.146886.112